Is creative work sustainable? Understanding identity, motivation, and worth - Reid, A.; Petocz, P.; Bennett, Dawn (Sage Publications, 2016)
The purpose of this article is to explore the “value” of creative workers’ work from their perspective. The work of this group is often ephemeral and intangible, contributes to the development of society, and is often very poorly remunerated. Qualitative responses from a large survey of creative workers’ work experience and attitudes have provided the material analyzed for this paper. The data were analyzed using a naturalistic coding process leading to the emergence of themes describing the data. Five “elements of worth” emerged which included identity representation, motivation, catalysts of creativity, interactions with society, and recognition. Knowing how creative workers experience these five elements provides educators and local/national policy makers data on which to base their pedagogical and financial judgments. To date, there has been no other study that examines how creative workers perceive the value of their work and how that notion of value is derived from their lived experience.